Analisis Pengaruh Kualitas Produk, Persepsi Harga, Dan Citra Merek Terhadap Keputusan Pembelian Sepatu Olahraga Merek Reebok Pada After.Disc Di Kota Semarang - Nuri Handoyo; Mochamad. Taufiq (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2021)
The purpose of this research is to find out the influence of product quality, price perception, and brand image on the purchasing decision of Reebok brand sports shoes in the After.disc shoes store. The population in this study are all consumers who come to After.disc shoes store. While the sample was chosen using the non-probability sampling method of 96 respondents. Data analysis methods used in this study include data instrument testing, model feasibility tests, t tests, and multiple linear regression analysis. The results of testing hypothesis 1 (H1) produce that product quality has a significant positive effect on purchasing decisions so that it can be interpreted the higher the quality of Reebok shoes sold by After.disc shoes store, the higher the tendency of consumers to make a decision to buy. Hypothesis 2 (H2) results show that price perception has a significant positive effect on purchasing decisions so that it can be interpreted as the more affordable Reebok shoes prices After.disc shoes store, the higher the tendency of consumers to make decisions to buy.